Markedly enhanced up-conversion luminescence by combining IR-808 dye sensitization and core–shell–shell structures. Issue 5 (16th January 2017) - Xu, Jiating; Sun, Mingdi; Kuang, Ye; Bi, Huiting; Liu, Bin; Yang, Dan; Lv, Ruichan; Gai, Shili; He, Fei; Yang, Piaoping
Abstract : The up-conversion emission of core–shell–shell structured nanoparticles has been greatly enhanced by IR-808 dye sensitization of 808 nm photons. Abstract : Rare-earth-doped up-conversion nanoparticles (UCNPs), which are capable of converting infrared light to shorter-wavelength photons, have attracted worldwide attention due to their unique characteristics. However, the emission brightness of UCNPs is greatly limited by the unsatisfactory absorptivity of lanthanide ions. Herein, we adopted a novel strategy to enhance the up-conversion intensity using NIR dye IR-808 as an antenna to sensitize the core–shell–shell structured NaGdF4 :Yb, Er@NaGdF4 :Yb@NaNdF4 :Yb UCNPs. When excited with 808 nm light, the IR-808 emitted a broadband peak, which perfectly overlapped with the absorption of Nd 3+ and Yb 3+ ions. Thus, the active shell of NaNdF4 :Yb can efficiently capture the emitted NIR photons and transfer them to the transition layer of NaGdF4 :Yb. The transition layer acted as an energy bridge to connect the active shell and up-converting zone, avoiding the energy back-transfer from the activators to Nd 3+ ions. The optimized dye sensitization combined with the well-designed core–shell–shell structure tremendously enhances the NIR photon absorptivity of UCNPs and eliminates the deleterious cross-relaxation between the activators and sensitizers, eventually leading to dramatic enhancement of the up-conversion intensity. This study provides a new insight into the dye-sensitized up-conversion luminescence of rare earth-based nanoparticles and facilitates their practical applications.